Public or Private/Home: Where and Why are Ill Neonates Sought out for Health Care? - Budha, Kamal Bahadur; Adhikari, Chiranjivi (Birat Journal of Health Sciences, 2022)
Introduction: Care seeking behavior is a process of taking actions in the pursuit of health gain and obtaining treatment. Various factors influence mothers to choose public or private health care facilities for neonatal health and illness, which may help policy makers to achieve the Universal Health Coverage (UHC). Objective: The study aimed to find out the factors associated with maternal care-seeking behaviors of their neonates’ health and illness. Methodology: A cross-sectional study was carried out among 248 mothers having neonates up to six months with the history of illness during their neonatal period, selected by applying 30 cluster sampling strategy. We entered data and then analyzed in SPSS with chi-square test and logistic regression methods. Results: Majority of ill neonates (68%) were sought out in public health facilities in Jumla. A few (6%) were taken to private facilities whereas more than one-fourth (28%) were either sought out nowhere or treated at home traditionally. Proportion of fever and acute respiratory infections (ARI) among neonates was almost half (46.4%) and one-fifth (19%), respectively. Multivariate logistics regression showed that mothers with primary education and above had an odds of 25 (95% CI, 1.44-333.0) , with a self-decision had an odds of 11.29 (95% CI, 2.26-56.00), and walking distance of ≤30 minutes to health facility had an odds of 104.2 (95% CI, 3.80-2821.4), for seeking out the remedy in public health facilities for their neonates. Conclusions: The study concluded that more than half neonates were ill from different diseases and more than two-thirds of them were taken to public health facilities to seek out for remedy. Maternal education having at least primary level, with a self-decision, and less distance to health facilities were the probable factors of choosing public health facilities for seeking out the remedy for a neonatal illness. Nonetheless, further studies with larger sample size and stronger designs are warranted for a firmer conclusion.